2017
DOI: 10.1098/rsos.161008
|View full text |Cite
|
Sign up to set email alerts
|

Heritable variation in colour patterns mediating individual recognition

Abstract: Understanding the developmental and evolutionary processes that generate and maintain variation in natural populations remains a major challenge for modern biology. Populations of Polistes fuscatus paper wasps have highly variable colour patterns that mediate individual recognition. Previous experimental and comparative studies have provided evidence that colour pattern diversity is the result of selection for individuals to advertise their identity. Distinctive identity-signalling phenotypes facilitate recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Identity signals are predicted to occur as fixed phenotypes with high degrees of genetic determination [5]. The few parent -offspring analyses that have been conducted on individual identity signals demonstrate high heritability [17,19].…”
Section: (C) Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Identity signals are predicted to occur as fixed phenotypes with high degrees of genetic determination [5]. The few parent -offspring analyses that have been conducted on individual identity signals demonstrate high heritability [17,19].…”
Section: (C) Developmentmentioning
confidence: 99%
“…Identity signals are predicted to occur as fixed phenotypes with high degrees of genetic determination [5]. The few parent -offspring analyses that have been conducted on individual identity signals demonstrate high heritability [17,19]. Additionally, identity signals are expected to have low costs associated with their production and maintenance because phenotypes that are not costly will spread to a higher equilibrium frequency than more costly phenotypes [5].…”
Section: (C) Developmentmentioning
confidence: 99%
“…Color patterns were not experimentally altered. Previous work has found that P. fuscatus color patterns tend to be more similar within nests than between nests (Sheehan et al., 2017).…”
Section: Methodsmentioning
confidence: 92%
“…Because wasps learn the unique facial patterns of each nestmate, they could potentially use facial patterns to discriminate between nestmates with known facial patterns and non‐nestmates with novel facial patterns. Further, nestmates tend to have more similar facial patterns than non‐nestmates, though there is still extensive facial pattern variation within each nest (Sheehan et al., 2017). Integrating information from both visual and chemical signals during nestmate recognition could enable wasps to make more accurate assessments about nestmate identity than relying on a chemical signals alone.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in sex chromosome, genes linked to the X-chromosome are transmitted to daughters and sons, whereas genes linked to the Y-chromosomes are only transmitted to sons. This method of matrix inversion is implemented in the R package nadiv (Wolak, 2012), which has been applied to wasps but never to honeybees (Sheehan et al, 2017). However, many traits under selection are genetically correlated and will not evolve independently from each other, due to linkage or pleiotropy (one loci influencing several traits).…”
mentioning
confidence: 99%